Simple piezoelectric ceramic generator-based electrospinning apparatus. Issue 70 (12th July 2016) - Duan, Xiao-Peng; Yan, Xu; Zhang, Bin; Zhang, Zhi-Guang; Yu, Miao; Zhang, Hong-Di; Yang, Da-Peng; Long, Yun-Ze
Abstract : A new simple e-spinning setup using a piezoelectric ceramic (PZT) generator as high voltage supply was designed and its performance on electrospinning several polymers was investigated. Abstract : The conventional high-voltage power supply (HVPS) used for electrospinning (e-spinning) is heavy and needs an extra electricity supply, which hinders the portability of the e-spinning apparatus. In this communication, we report on a new simple e-spinning setup using a piezoelectric ceramic (PZT) generator to replace HVPS, which makes the setup very simple, and may be the simplest e-spinning apparatus (small volume 5 × 1 × 1 cm 3 and light weight < 10 g). The pulsed voltage generated by a PZT element is about 56 kV, which can meet the requirement for e-spinning. Three kinds of polymer solutions such as polyvinylpyrrolidone (PVP), poly(vinylidene fluoride) (PVDF) and polystyrene (PS) have been electrospun into ultrathin fibers successfully, which confirms the feasibility of this apparatus. The influences of different parameters such as e-spinning distance (1–9 cm) and solution concentration (11–14 wt%) were investigated. This work demonstrates a new approach to design a portable and simple e-spinning apparatus.